Demonstration of kilohertz operation of hydrodynamic optical-field-ionized plasma channels - Alejo, A; Cowley, J; Picksley, A; Walczak, R; Hooker, SM (American Physical Society, 2022)
We demonstrate experimentally that hydrodynamic optical-field-ionized (HOFI) plasma channels can be generated at kHz-scale pulse repetition rates, in a static gas cell and for an extended period. Using a pump-probe arrangement, we show via transverse interferometry that the properties of two HOFI channels generated 1 ms apart are essentially the same. We demonstrate that HOFI channels can be generated at a mean repetition rate of 0.4 kHz for a period of 6.5 h without degradation of the channel properties, and we determine the fluctuations in the key optical parameters of the channels in this period. Our results suggest that HOFI and conditioned HOFI channels are well suited for future high-repetition rate, multi-GeV plasma accelerator stages.